Characterization of an mRNA-Encoded Antibody Against Henipavirus - Zixuan Liu; Bingjie Sun; Ting Fang; Xiaofan Zhao; Yi Ren; Zhenwei Song; Sijun He; Jianmin Li; Pengfei Fan; Changming Yu (Current Issues in Molecular Biology, 2025)
Nipah and Hendra viruses are lethal zoonotic pathogens with no approved vaccines or therapeutics. mRNA produced via in vitro transcription enables endogenous protein expression and cost reduction. Here, we systematically screened natural and artificial untranslated regions (UTRs) and identified an optimal combination for expressing henipavirus-neutralizing antibody 1E5. We generated mRNA-1E5 encapsulated in lipid nanoparticles (mRNA-1E5-LNPs). In vitro, mRNA-1E5-LNPs achieved functional antibody expression levels of >1500 ng/mL. In BALB/c mice, intravenous administration of mRNA-1E5-LNPs induced rapid antibody elevation (peak at day 3), without hepatic toxicity or tissue inflammation. We established two Hendra pseudovirus models in biosafety level 2 facilities to evaluate the efficacy of mRNA-1E5-LNPs. Low-dose prophylactic administration effectively blocked entry of the Hendra pseudovirus. Notably, a single 0.5 mg/kg dose of mRNA-1E5-LNPs, stored at 4 °C for two months and administered 7 days prior, provided good protection. Our findings provide a therapeutic strategy for henipaviral infections and a blueprint for the development of mRNA-based antibodies against emerging viruses.